2023
DOI: 10.3390/life13041011
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning Methods in Identifying Genes Associated with COVID-19 in Cardiomyocytes and Cardiac Vascular Endothelial Cells

Abstract: Corona Virus Disease 2019 (COVID-19) not only causes respiratory system damage, but also imposes strain on the cardiovascular system. Vascular endothelial cells and cardiomyocytes play an important role in cardiac function. The aberrant expression of genes in vascular endothelial cells and cardiomyocytes can lead to cardiovascular diseases. In this study, we sought to explain the influence of respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on the gene expression levels of vascular endothelial cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 131 publications
0
1
0
Order By: Relevance
“…Cardiovascular disorders can be caused by atypical gene expression in vascular endothelial cells and cardiomyocytes, which are crucial in regulating heart function. Numerous genes were found to be differentially expressed in cardiomyocytes and vascular endothelial cells of COVID-19-infected heart patients as reported by Xu et al, including MALAT1, CD36, LARGE1, RYR2, PLCG2 (in cardiomyocytes), MALAT1, ID1, ID3, MT-CO1 and EGFL7 (in vascular endothelial cells) (87) . These genes regulate many vital functions in these cardiac cells (88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103) .…”
Section: Genetics Of Covid19-induced Heart Complicationssupporting
confidence: 61%
“…Cardiovascular disorders can be caused by atypical gene expression in vascular endothelial cells and cardiomyocytes, which are crucial in regulating heart function. Numerous genes were found to be differentially expressed in cardiomyocytes and vascular endothelial cells of COVID-19-infected heart patients as reported by Xu et al, including MALAT1, CD36, LARGE1, RYR2, PLCG2 (in cardiomyocytes), MALAT1, ID1, ID3, MT-CO1 and EGFL7 (in vascular endothelial cells) (87) . These genes regulate many vital functions in these cardiac cells (88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103) .…”
Section: Genetics Of Covid19-induced Heart Complicationssupporting
confidence: 61%
“…The involvement of vascular endothelial cells and cardiomyocytes is crucial in regulating heart function, and cardiovascular disorders can arise as a result of the atypical expression of genes in vascular endothelial cells and cardiomyocytes. Xu et al have recently identified many genes that are differently expressed in cardiomyocytes and vascular endothelial cells of heart patients infected with COVID-19, including MALAT1, CD36, LARGE1, RYR2, PLCG2 (in cardiomyocytes), MALAT1, ID1, ID3, MT-CO1 and EGFL7 (in vascular endothelial cells) (87) . These genes regulate many vital functions in these cardiac cells (88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103) .…”
Section: Long-term Cardiovascular Results With Covid-19 Pearlsmentioning
confidence: 99%
“…This sustained change could result in increased thrombotic complications and atherosclerotic disease progression, akin to long COVID-19. [36][37][38][39][40] The early elevation in CD163, on the other hand, may be a compensatory and important scavenger receptor for free hemoglobin limiting tissue injury. However, significant elevations have been demonstrated in patients with severe sepsis going on to develop organ failure.…”
Section: Discussionmentioning
confidence: 99%